Corporate social responsibility or strategic opportunism? Evidence from High and New Technology Firms - Deng, Yang; Di Vaio, Assunta; Ong, Tze San (John Wiley and Sons, 2025)
Corporate Social Responsibility (CSR) presents a dual nature in practice. Beyond its explicit ethical imperatives, it can be strategically instrumentalized to manage external pressures, shape public impression, and even divert attention from corporate misconduct. Acknowledging this complexity, this study investigates the conditions under which CSR is leveraged as a strategic tool and how this distinction relates to earnings management (EM). Drawing on agency theory and instrumental stakeholder theory, this study examines 2973 Chinese High and New Technology Firms (HNTFs) from 2017 to 2021 and clarifies the boundary conditions under which a positive CSR–EM association is more plausible, namely, when CSR is predominantly symbolic/instrumental rather than substantive/genuine. This study also tests whether media attention moderates this linkage. It finds a positive association between CSR and EM concentrated in the social and governance pillars, consistent with the use of CSR as reputational insurance and impression management; the environmental pillar shows no meaningful association. Greater media attention strengthens the CSR–EM association, suggesting firms increase visible CSR to meet external expectations while simultaneously managing reported performance. Importantly, this evidence does not dispute substantive/genuine CSR; rather, it highlights conditions under which CSR may be instrumentalized, underscoring the need to differentiate substantive from symbolic engagement.